Time of day has no influence on performance and pacing during a 4 km cycling time trial - Zadow, E. K.; Kitic, C. M.; Wu, S. S. X.; Abbiss, C. R.; Peiffer, J. J.; Fell, J. W. (Sports Medicine Australia, 2016)
Background: Time of day has been shown to impact athletic performance with changes of up to 10% detected throughout the day. Physiological factors such as body temperature and hormonal responses display individual circadian rhythms and are believed to be associated with alterations in performance. These factors may also contribute to variations in the distribution of power throughout an event (pacing), however, we are aware of only one study that has investigated the influence of time of day on pacing. Therefore, the aim of this study was to investigate the influence of time of day on pacing selection within a 4 km cycling time trial. Methods: Seventeen trained male cyclists (age: 40.0 ± 10.4 y, weight: 78.3 ± 9.1 kg, height: 181.3 ± 6.1 cm, VO2max: 62.7 ± 8.3 ml.kg-1.min-1) performed five 4 km cycling time trials (TTs) over five different times of the day (08:30, 11:30, 14:30, 17:30 and 20:30 h). All trials were completed on their own bicycles attached to a cycle trainer (KICKR: Wahoo Fitness, Atlanta, GA), in a randomised order, with each trial separated by a minimum of two and a maximum of seven days. Pacing was assessed through the collection of power, cadence, heart rate and oxygen consumption at 0.5 km averages throughout each TT. Ratings of perceived exertion (RPE: 6-20) and effort (0-10) were collected immediately post-TT. Power, heart rate and oxygen consumption were analysed using two-way repeated measures analysis of variance (Time of Day x distance). Mean power, heart rate and cadence, total time, RPE and effort were analysed using a one-way repeated measures analysis of variance. Results: No differences in overall mean power output, cadence, total time, heart rate and RPE were observed between TTs performed at 08:30, 11:30, 14:30, 17:30 and 20:30 h (p>0.05). Reported effort was significantly higher for the 08:30, 11:30 and 20:30 TTs compared with TTs performed at 14:30 (p<0.05) and was also significantly higher at 20:30 compared to the 17:30 trial (p<0.05). No differences in pacing were observed during the 4 km TTs throughout the day (p>0.05). Discussion: This study found no differences in pacing or performance during a 4 km TT at different times of the day. In well-trained athletes, pacing strategy is likely to be more consistent and small within-subject coefficient of variability for performance may have masked any circadian rhythm effects. The differences in perceived effort is novel, but did not appear to influence pacing or performance.